Latent profiles of post-traumatic distress and growth in adolescents: the role of modifiable protective factors - Yang, Haiying; Sun, Lihong; Zhang, Ying (Frontiers in Psychiatry, 2026)
ObjectiveThis study examined heterogeneous patterns of trauma-related adaptation among Chinese adolescents during the post–COVID-19 recovery phase, focusing on the co-occurrence of posttraumatic distress (PTD) and posttraumatic growth (PTG). We also investigated how modifiable psychosocial protective and vulnerability factors were associated with membership in different adaptation profiles.MethodA large-scale cross-sectional survey was administered to 5, 044 students (aged 9–17 years; 46.6% male) from 15 primary and secondary schools in Wuhan, China. Validated instruments assessed posttraumatic stress symptoms (PCL-C), posttraumatic growth (PTGI), depressive symptoms (CES-D), and anxiety (SAS). Protective and vulnerability factors included resilience (CD-RISC), perceived social support (SSRS), physical activity (PARS-3), school belonging (PSSM), adaptive coping (SCSQ), and trait anxiety (TAI). Latent profile analysis (LPA) was used to identify adaptation profiles, and multinomial logistic regression examined how modifiable psychosocial factors were associated with profile membership.ResultsLPA revealed four empirically derived profiles: a High Distress/High Growth–Moderate PTSD profile (76.9%), a Low Distress–High Growth profile (4.8%), a Low Growth–Moderate Distress profile (3.9%), and a High Distress/High Growth–High PTSD profile (14.4%). The vast majority of adolescents showed some degree of both PTD and PTG, consistent with dual-process perspectives. In multinomial models, higher resilience, social support, school belonging, adaptive coping, and physical activity were associated with greater likelihood of belonging to the Low Distress–High Growth profile rather than more distressed profiles, whereas higher trait anxiety was associated with increased odds of membership in profiles characterized by greater distress.ConclusionsIn this large school-based sample of Chinese adolescents, distress and growth frequently co-occurred and clustered into distinct adaptation profiles that differed systematically in psychosocial resources. Resilience, social connectedness, school belonging, and physical activity emerged as promising targets for trauma-informed, school-based support, whereas trait anxiety appeared to mark heightened vulnerability. Given the cross-sectional and single-region design, these findings should be interpreted as exploratory, and longitudinal and cross-cultural studies are needed to clarify temporal and contextual influences on adolescent trauma adaptation.